(untitled) (مجلة المنصور, 2022)
The synchronizing and damping torque coefficients in the range of the electromechanical oscillation frequencies provide a measure of the generators’ contribution towards power system stability under small deviations, and may be taken as stability indices even for multi machine systems, although their interpretation is rather complex in this case. This paper presents the effect of Power System Stabilizer (PSS) on the synchronizing and damping torque coefficients for a synchronous generator connected to an infinite busbar through impedance; it explicitly includes the effects of its Automatic Voltage Regulator (AVR) and of the additional stabilizer signal derived from the rotor speed. Results obtained were compared with the conventional (AVR) using MATLAB 7 programming language.